Inhibition of microRNA-128-3p alleviates liver ischaemia–reperfusion injury in mice through repressing the Rnd3/NF‐κB axis. Issue 6 (August 2020) - Mou, Tong; Luo, Yunhai; Huang, Zuotian; Zheng, Daofeng; Pu, Xingyu; Shen, Ai; Pu, Junliang; Li, Tingting; Dai, Jiangwen; Chen, Wei; Wu, Zhongjun
Although liver ischaemia–reperfusion (I/R) injury remains the primary underlying reason for liver transplant failure or post-transplantation liver dysfunction, the underlying mechanism is still largely elusive. MicroRNAs (miRNA) are involved in multiple physiological and pathological processes, including inflammation. Here, we identified that the miR-128-3p/Rho family GTPase 3 (Rnd3)/NF‐κB axis might play a critical role in liver I/R injury. Our results demonstrated that the level of miR-128-3p was negatively correlated with the Rnd3 level during liver I/R. Dual luciferase reporter assay results proved that Rnd3 mRNA was a direct target of miR-128-3p. Additionally, Western blotting and quantitative RT-PCR analyses revealed that knock-down of miR-128-3p could up-regulate Rnd3 mRNA and protein levels, thereby suppressing the NF-κB pathway through down-regulating NF‐κB p65. Consequently, the serum levels of NF-κB–associated inflammatory factors and aspartate aminotransferase/alanine aminotransferase were decreased. Moreover, overexpression of Rnd3 could reverse the activation of NF-κB caused by miR-128-3p agomir during liver I/R injury. Overall, our study results suggest that repression of miR-128-3p can alleviate liver I/R injury through the miR-128-3p/Rnd3/NF‐κB axis and may facilitate the development of novel protective approaches against liver I/R injury.